Validitas Booklet pada Materi Analisis Proksimat Guna Meningkatkan Keterampilan Proses Sains Peserta Didik SMK Kompetensi Keahlian Kimia Analisis - Salsabila Ameilia As-Sahra; Rusmini Rusmini (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2025)
This research aims to develop and validate a booklet on proximate analysis to enhance the science process skills (SPS) of vocational high school students majoring in chemical analysis. The study employs a Research and Development (R&D) approach, specifically using the 4D model (Define, Design, Develop, and Disseminate), although this research is limited to the Develop stage. The Define stage involved needs analysis, student analysis, task analysis, and concept analysis. The Design stage focused on media selection (booklet), format selection based on SPS indicators, and initial booklet design, including components like cover, content list, learning objectives, and practice questions. The Develop stage involved expert validation by two chemistry lecturers and one chemistry teacher, assessing content and construct validity using a Likert scale (1-5). The booklet was deemed valid if the mode of the scores from all validators was in the "good" or "very good" category. The results showed that the booklet achieved a "very good" rating for content validity, including the accuracy of the material, alignment with learning objectives, relevance to current scientific developments, suitability of practicum activities, and the appropriateness of practice questions. Construct validity, assessing the presentation, layout, and readability, also received a "very good" rating. Overall, the validation results indicate that the developed proximate analysis booklet is valid and suitable for improving the science process skills of vocational high school students in chemical analysis. The booklet is deemed ready for the next stage of research, which is implementation in the classroom.